Early Experiences with Management of Extra Hepatic Portal Vein Obstruction - Rawal, Sushil Bahadur; Malla, Srijan; Giri, Naresh Kumar; Rayamajhi, Jyoti; Shah, Kunda (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Extrahepatic portal vein obstruction (EHPVO), a rare condition, is increasingly being diagnosed due to easier availability of proper diagnostic tools and early referrals. Here we report our series of 16 cases of EHPVO who were treated at our hospital. The aim of this paper is to share our early experiences of managing this rare and difficult condition. Methods: A retrospective analysis of patients’ records admitted with the diagnosis of EHPVO for a period of 18 months from Jan 2008 to June 2010 was performed. Patients were followed up for at least 9 months, their demographic data and outcome of surgery was analysed. Results: Of the 10 cases fulfilling the inclusion criteria, 9 underwent surgical therapy. Distal lienorenal shunt was performed in 4 patients, proximal lienorenal shunt in 2 patients and devascularisation procedure in 3 patients. Rebleeding was seen in 2 patients. The prognosis of EHPVO was good in patients without a severe underlying disease at a median follow up of 9 months. Conclusion: Conventional surgical therapies have a good outcome in management of EHPVO in our context. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/4-6 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7898